A minerochemical cement study of a beachrock slab: The case study of Peristeria, Salamis Island - Saitis, G.; Evelpidou, N.; Kawasaki, S.; Koutsopoulou, E.; Komi, A. (15th International Congress of the Geological Society of Greece, 2019)
Beachrocks are consolidated sedimentary formations and are composed of coastal sediments, which are cemented through the precipitation of carbonates. The lithification takes place in the intertidal zone and can include various sediments, such as sands and gravels of clastic and biogenic origin. This study deals with the cements’ mineralogical and geochemical features of a beachrock outcrop and its aim is the contribution for further understanding on the cementation process of beachrocks. (e.g. Vieira and Ros, 2007; Vousdoukas et al., 2007; Karkani et al., 2017).